2015
DOI: 10.3906/sag-1312-149
|View full text |Cite
|
Sign up to set email alerts
|

Is there any impact of PET/CT on radiotherapy planning in rectalcancer patients undergoing preoperative IMRT?

Abstract: Background/aim: To investigate the effect of positron emission tomography-computed tomography (PET/CT)-based contouring on dosimetric parameters in rectal cancer patients undergoing preoperative intensity-modulated radiation therapy (IMRT). Materials and methods:Preoperative radiation therapy plans with conformal radiotherapy (CRT) or IMRT were created and examined according to the CT-and PET/CT-based contouring of 20 rectal cancer patients, retrospectively. Results:The target volumes delineated with PET/CT we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…[26][27][28] Moreover, some encouraging dosimetric results have highlighted the potential role of positron emission tomography/CT-based planning approaches in neoadjuvant radiotherapy for rectal cancer. 29 The clinical impact of such approaches is yet to be shown prospectively. 30 Several limitations should be considered when interpreting the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Moreover, some encouraging dosimetric results have highlighted the potential role of positron emission tomography/CT-based planning approaches in neoadjuvant radiotherapy for rectal cancer. 29 The clinical impact of such approaches is yet to be shown prospectively. 30 Several limitations should be considered when interpreting the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The only study where PET/CT delineated larger volumes, 51•74 cm 3 , than CT, 46•26 cm 3 (p = 0•043), measured the clinical target volume (CTV) which encompasses both GTV and an additional margin to cover for microscopic tumour spread. 40 Comparisons of different PET/CT volume delineation methods demonstrated that auto-delineated (contoured) volumes were significantly smaller than subjective interpretation performed using visual inspection or manual delineation. 35 Whereas, gradient-based (GR) auto-contouring method defined smaller TVs than signal-to-background ratio (SBR) auto-contouring method.…”
Section: Journal Of Radiotherapy In Practicementioning
confidence: 96%
“…Only one 33 out of the eight studies selected for the review mentioned the study design used. [34][35][36][37][38][39][40] Two of the included studies were conducted using prospective design. The included studies involved 261 patients with LARC.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Anderson et al 73 showed that the mean [ 18 F]FDG-PETbased GTV was smaller than the CT-based GTV, resulting in a change in PTV in 17% of 23 patients. The real strength however of using [ 18 F]FDG-PET to optimise target volume definition lies in the co-registration of [ 18 F]FDG-PET with other imaging techniques such as CT or MRI, to delineate a more accurate biological target volume, as was demonstrated by several groups 70,[74][75][76][77][78][79][80] . The use of co-registered [ 18 F]FDG-PET/CT indeed showed a higher uniformity between observers' definition of the GTV in a study of 6 patients 74 .…”
Section: Rectal Cancermentioning
confidence: 99%